Dielectric properties of binary hydrofluoroolefin refrigerant mixtures: Comparisons of new experimental data with molecular dynamics simulations. (January 2020) - Raabe, Gabriele; Hopkins, Matthew G.; Sampson, Catherine C.; Stanwix, Paul L.; May, Eric F.
Abstract: The introduction of new refrigerants based on HFO compounds such as trans-1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) and 2, 3, 3, 3-tetrafluoropropene (R1234yf) requires information on their dielectric properties to understand their interactions with electrically-live parts of thermal systems. Furthermore, the application of these HFOs as components in blends gives rise to the need for reliable approaches for predicting the dielectric properties of such mixtures. We report experimental data for the dielectric permittivity and polarization of the mixtures (0.50 R1234yf + 0.50 R1234ze(E)) and (0.89 R1234yf + 0.11 R1234ze(E)) over a temperature range from (250 to 366) K and pressure range from (0.6 to 10.0) MPa. The experimental data are used to test the applicability of a semi-theoretical correlation for the molar polarizability of the pure fluids, presented in our earlier work, combined with a mixing rule from the literature to estimate the dielectric properties of the mixtures. Additionally, we analyse the performance of a hybrid modelling approach for the dielectric permittivity, which is based on molecular simulation with a correction to account for the effect of each molecule's electronic polarization. Two different approaches to calculating the correction term are investigated, either incorporating experimental molecular polarizability data or data from ab initio simulations. The comparison shows that the empirical mixing rule approach decreases in accuracy as mixing effects become increasingly pronounced, whereas the molecular simulations describe the mixtures as well as they do the pure fluids. However, the molecular simulations are limited by their under-prediction of the dielectric permittivity of R1234yf at liquid densities above 9.5 kmol∙m −3 .